2015
DOI: 10.1148/radiol.14140364
|View full text |Cite
|
Sign up to set email alerts
|

High Signal Intensity in Dentate Nucleus on Unenhanced T1-weighted MR Images: Association with Linear versus Macrocyclic Gadolinium Chelate Administration

Abstract: Hyperintensity in the DN on unenhanced T1-weighted MR images is associated with previous administration of linear GBCA, while the previous administration of macrocyclic GBCAs showed no such association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
275
1
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 427 publications
(309 citation statements)
references
References 24 publications
26
275
1
4
Order By: Relevance
“…Gadolinium presence was originally observed in bone [5,6,30] and more recently in the brain [7][8][9][31][32][33][34][35][36][37][38][39] in patients with normal renal function.…”
Section: Gadolinium Storage Conditionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gadolinium presence was originally observed in bone [5,6,30] and more recently in the brain [7][8][9][31][32][33][34][35][36][37][38][39] in patients with normal renal function.…”
Section: Gadolinium Storage Conditionmentioning
confidence: 98%
“…It may be that difficulty with processing and/or metabolizing metals, or over-reaction to them, may be primarily a European-origin Caucasian person's disease. As further indirect proof of GDD being a predominantly white person's genetic disease, the initial and subsequent publication of gadolinium retained in the dentate nucleus and globus pallidus was made by Kanda et al [31] on a Japanese population, hence simple storage is likely a universal phenomenon of gadolinium exposure, and especially of linear agents [33,34,[36][37][38][39]. Yet there are no major series of NSF coming from Japan, South Korea or China [51,52].…”
Section: Epidemiologymentioning
confidence: 99%
“…4) [106][107][108]. Because of the toxicity of gadolinium, residual gadolinium has been attracting increasing attention [109][110][111][112][113][114][115][116]. These regions show increased signal with the administration of linear-type GBCAs but not macrocyclic-type GBCAs; because linear-type GBCAs are more unstable , and pulvinar of thalamus (yellow arrows) are hypointense compared with a normal agematched female (Fig.…”
Section: Gadoliniummentioning
confidence: 99%
“…Different ratios have been used for quantitative measurements including DN-to-pons, DN-to-middle cerebellar peduncle, DN-to-cerebellar white matter, DN-to-CSF, DN-to-corpus callosum genu (CC), GP-to-Th, GP-to-CSF, GP-to-CC, Th-to-CC, and Caudate nucleus-to-CC [1][2][3][4][5][6][7][8][9][17][18][19][20]. In a study with healthy volunteers, T1 SI of DN, pons, GP, white matter, and gray matter were all evaluated and normalized with CSF [21].…”
Section: Quantitative Ratios Measurementsmentioning
confidence: 99%
“…In the past 2 years several magnetic imaging (MRI) studies reported high T1 signal intensity in the dentate nucleus (DN) and/or globus pallidi (GP) in patients with normal renal function after multiple administrations of gadolinium-based contrast agents (GBCAs) suggesting gadolinium deposition [1][2][3][4][5][6][7][8][9]. The agent most commonly implicated was gadodiamide (Omniscan ® ) a non-ionic linear agent, classified according to its stability as a weak agent [10], followed by gadopentetate dimeglumine (Magnevist ® ) and gadobenate dimeglumine (MultiHance ® ), both ionic linear agents, classified as agents with intermediate stability [10].…”
Section: Introductionmentioning
confidence: 99%